Are we capable enough to innovate?: A case study of HS Tech Sdn. Bhd - Selvam, Heramban; Imaduddin, Abidin; Muhamad Tamyez, Puteri Fadzline (Penerbit Universiti Malaysia Pahang, 2022)
Innovation is at the heart of company activity, based on the continuous technological development of products and services. However, a few only consistently measure their innovation capabilities to ensure sustainability in competitiveness. Through a single case study, an innovation fitness assessment was used to evaluate the innovation capabilities, and interviews has been conducted to determine how they further manage their innovation. The themes that emerged were quality assurance, culture and climate, structures and systems, organizational intelligence, harnessing the competence base, and research and development. In general, all scores of the innovation assessment are over average, except for processes. Areas of improvement should be more focused on the innovation process. It is recommended for companies that are engaged in the innovation management process, and the importance of conducting their innovation fitness. Focusing on these 6 dimensions of innovation capability will increase their competitiveness.